Difusión cultural de logotipos sobre el buen cuidado del medio ambiente para una mejor vida de los niños y niñas de la escuela fiscal mixta Pichincha del barrio Salacalle del cantón Saquisili de la provincia de Cotopaxi del periodo 2012-2013 - Toapanta Molina, Rosa Elizabeth (2015)
Face with the need to reduce environmental degradation, this research proposes the cultural diffusion of logos to take care the environment which will allow to foster it. The Education from an early age will help to acquire rights and environmental responsibilities, the proposal to this work includes the structuring of representative graphic material with informative contain for the children of the Pichincha fiscal school, through simple actions that promote the reduction of waste, the reuse of products extending its useful life and finally recycling as possible and time mainly in the management of the natural resources of one representative properly. For environmental conservation, held craft workshops using recycled materials and implementation of stations of recycling through which it will contribute to take care of the environment….